Forensic fractography of bone: fracture origins from impacts, and an improved understanding of the failure mechanism involved in beveling - Christensen, Angi M.; Rickman, John M.; Berryman, Hugh E. (University of Florida Press, 2021)
Fractography involves the study of fractures and cracks in a material in order to understand the cause of failure. Even as a complex, highly hierarchical composite, bone is a material that obeys physical laws, including cracking behavior. The fields of fractography and fracture mechanics, therefore, have much to offer in our understanding of bone’s response to loading and force. Here we discuss how fractography can be used in the assessment of fractures originating from impacts including those from projectiles. Fractures and fracture patterns frequently associated with impact trauma—including radial fractures, circumferential fractures, and beveling—are described and used interpretively in forensic analyses; however, the mechanisms for their production and arrangement are often underutilized in fully understanding the trauma event. These mechanisms are reviewed here from a fractography perspective. Furthermore, a review is presented of new data indicating that beveling in bone associated with impacts, especially with projectiles, is produced by cone cracking, a process that is also well documented in other brittle materials. This information can be used to enhance understanding of impact trauma in general, as well as in the context of specific forensic cases. Moreover, describing and interpreting skeletal trauma within the context of fracture mechanics and fractography has the advantage of aligning the nomenclature used in forensic anthropology with that used in other scientific fields, particularly those involved in the study of material failure. To facilitate this alignment, we provide discussion and definitions for various fractography-related terms.
Keywords: fractography; beveling; skeletal trauma; impacts; fracture mechanics; cone cracking